“O Messias sou eu”: a hermenêutica da religião em Lévinas (“I am The Messiah ": the hermeneutics of religion in Levinas). DOI: 10.5752/P.2175-5841.2013v11n29p175 - Paiva, Márcio Antônio (Horizonte, 2013)
The expression "I am the messiah" applies to the ethical relationship as the first task of the messiah: the subjectivity of the own subject. Through rabbinic commentaries from the Talmud, Levinas brings us a hermeneutic that understands ethics as proximity and responsibility, irreplaceable and inalienable by others. In this sense, the Hebrew notions of messianism and prophetic words, taken from the midrash within the rabbinic hermeneutics, allow us to advance on the idea of religious language in its original sense: ethics. Such notions are metaphors that take the thought to reveal itself in other ways. In the comments of the Talmud there is no place for religious enthusiasm or for any sort of rapture of mystical nature. But, there is indeed, a place for a rigorous hermeneutic that it is in permanent search for a kind of meaning that is always beyond. This way of understanding the religious experience leaves the sacred numinous and understands transcendence as ethics. In this sense the thought appears marked by the experience of the man who is seen as hostage to each other. This man is necessary to the other man, since without him the moral would never start anywhere. Within Levinas perspective, ‘I am’ this contemporary and elected messiah.